Leveraging Virtual Desktop Infrastructure to Improve Workforce Productivity and Flexibility - Ahmad Syafruddin Indrapriyatna; Muhammad Andrian Fadillah; Rahmat Budiarto; Ikhwan Arief (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
Despite the widespread adoption of Virtual Desktop Infrastructure (VDI), empirical evidence on its organizational impact—particularly in developing-country contexts—remains limited, with prior studies largely focusing on technical performance rather than workforce outcomes. This study addresses this gap by evaluating the impact of VDI implementation on work efficiency and employee mobility in a real organizational setting. We provide empirical evidence from a real-world deployment that demonstrates how VDI contributes to measurable improvements in workforce performance in a resource-constrained environment. A mixed-method approach was employed, combining quantitative survey data and qualitative insights. User perceptions were measured before and after VDI implementation using a five-point Likert scale across key indicators, including system performance, accessibility, user satisfaction, flexibility, and workflow continuity. The results reveal a significant increase in the mean score from 14.75 to 21.67, indicating substantial improvements in system usability and access flexibility. The findings demonstrate that centralized desktop management reduces technical variability, enhances system consistency, and enables seamless remote access, thereby improving workflow continuity and supporting distributed work practices. This study provides one of the few empirical evaluations of VDI implementation in a real-world organizational setting within a developing-country context.